Research subjects and hot topics of foil bearings performance in recent twenty years: analysis and prediction - Zhou, Quan; Zhang, Yi; Hou, Yu (Forschung im Ingenieurwesen, 2021)
As one kind of gas bearings, foil bearings that are commonly made of one top foil and at least one bottom foil, have many attractive advantages such as low power loss, wide work temperature range, high rotating speed, low maintenance cost, simple system construct, etc. Nevertheless, foil bearings also have some disadvantages including low carrying load at low speed, wear at start-stop procedure, not easy to predict bearing performance due to the complex bearing structure and so on. For the sake of better understanding and further utilization of foil bearings, many researchers, institutions and countries have paid great attention to study these special rolling elements in recent decades. The purpose of this paper is to explore the research status of foil bearings performance based on the Web of Science datasets and related tools, meanwhile, the cooperative relationship among individuals or organizations is further studied. Moreover, to figure out influential countries, institutions and authors, the analysis of cited frequency is adopted. In addition, keywords frequency analysis and co-occurrence analysis are applied to explore the future trend of foil bearing. The results identify influential countries, institutions and authors in the research of foil bearings performance and show that whether in quantity or in quality, research of foil bearings performance in developed countries holds a significant lead over that in developing countries. Moreover, the current hot topics are figured out as well as future direction of development is predicted. This study presents intuitive state of research of foil bearings performance and proposes a fresh perspective for relevant researchers to perform foil bearings research in the future.